Teachers’ perception of the relationship as a moderator between victimization and life satisfaction - Bitinaite, Rugile; Dirzyte, Aiste; Indrasiene, Valdone; Jegeleviciene, Violeta; Merfeldaite, Odeta; Prakapas, Romas; Railiene, Asta; Gusauskiene, Marina; Serapinas, Danielius (Frontiers in Education, 2025)
IntroductionAlthough teacher victimization has been associated with reduced well-being, little is known about how teachers’ perceptions of their relationships within the school environment is linked to this association. This study examined whether perceived relationship quality moderates the link between different forms of victimization and teachers’ life satisfaction.MethodsA structural equation model was tested using data from a Lithuanian teacher sample (n = 1,146), incorporating three latent constructs: victimization (indicated by physical, social, verbal, cyber, and sexual victimization, as well as victimization involving property damage and violence perpetrated by school staff and parents), relationship perception (measured by perceived relationships with students, colleagues, school administration, and local educational authorities), and life satisfaction (assessed via the satisfaction with life scale).ResultsThe model demonstrated good fit [χ2(39) = 310.00, CFI = 0.941, TLI = 0.916, SRMR = 0.047, RMSEA = 0.078 (0.070, 0.086)]. Victimization was negatively related to both relationship perception (β = −0.35) and life satisfaction (β = −0.25), while relationship perception positively related to life satisfaction (β = 0.44, all p < 0.001). Moderation analyses revealed significant interaction effects: cyber, property, and physical victimization were more strongly associated with reduced life satisfaction among teachers who reported high perceived relationship quality with students or educational authorities. Contrary to buffering expectations, perceived relationships appeared to intensify the negative effects of victimization on life satisfaction.DiscussionThese findings suggest that victimization may be especially damaging for teachers who typically view their school relationships as supportive, pointing to a potential breach in relational expectations. This highlights the importance of contextual factors in teacher well-being.